2021
DOI: 10.1016/j.transproceed.2021.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of COVID-19 Infection in 2 Early Post-Liver Transplant Recipients

Abstract: Background Coronavirus disease 2019 (COVID-19) has affected all facets of life and continues to cripple nations. COVID-19 has taken the lives of more than 2.1 million people worldwide (23), with a global mortality rate of 2.2% (23). Current COVID-19 treatment options include supportive respiratory care, parenteral corticosteroids, and Remdesivir. Although COVID-19 is associated with increased risk of morbidity and mortality in patients with comorbidities, the vulnerability, clinical course, optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Two patients who underwent liver transplant and were infected with SARS-Cov-2 in the early post-transplant period were reported to be successfully treated with hydroxychloroquine, methylprednisolone, tocilizumab, and convalescent plasma [ 94 ]. Twenty-seven lung transplant recipients with moderate/severe COVID-19 received hydroxychloroquine (84%) in the early period of the COVID-19 pandemic, but the treatment protocol changed over time according to the new evidence of COVID-19 therapy [ 91 ].…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients who underwent liver transplant and were infected with SARS-Cov-2 in the early post-transplant period were reported to be successfully treated with hydroxychloroquine, methylprednisolone, tocilizumab, and convalescent plasma [ 94 ]. Twenty-seven lung transplant recipients with moderate/severe COVID-19 received hydroxychloroquine (84%) in the early period of the COVID-19 pandemic, but the treatment protocol changed over time according to the new evidence of COVID-19 therapy [ 91 ].…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…Two liver transplant recipients with COVID-19 in the early post-transplant period were successfully treated with tocilizumab (and hydroxychloroquine, methylprednisolone, convalescent plasma), with no signs of graft rejection [ 94 ]. Another case series of six SOT recipients reported a mortality rate of 33%, with no response to IL-6 blockade, remdesivir, and/or convalescent plasma [ 102 ].…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…Drug-induced hepatic injury related to COVID-19 treatment is also possible. Some early reports of Remdesivir treatment for COVID-19 included increased transaminases and bilirubin 14 , but meta-analysis of multiple reports 15 and studies in the pediatric 16 and transplant populations 17 , 18 found no increased risk of liver injury. Pancreatic injury is also multifactorial and hypothetically due to cytotoxicity of the virus via ACE-2 receptors in the pancreas, drug-induced injury, and damage secondary to the cytokine storm caused by immune dysregulation in severe infections 19 .…”
Section: Introductionmentioning
confidence: 99%
“… [31] Dale et al described two cases of early liver transplant who contracted severe COVID-19 and recovered. [32] Liver transplants had bad outcome, mostly related to co-morbidities and not due to immunosuppression. [33] In a contrasting observation, there are also reports of mild illness.…”
Section: Discussionmentioning
confidence: 99%